The generic analysis and specific structure of Carabidae of stepp areas of South Russia and northeast Azerbaijan - G. M. Abdurakhmanov; S. M. Klicheva (Юг России: экология, развитие, 2015)
The generic and specific composition of this areas Carabidae is analysed in this research